Legenda Mbah Sogol dan Cikal Bakal Gondanglegi Malang - Khuzaimah Khuzaimah; Kholik Kholik (Pusat Riset dan Inovasi Nasional, 2025)
This study describes a person who became a role model in the city of Gondanglegi